Acute Financial Hardship and Voter Turnout: Theory and Evidence from the Sequence of Bank Working Days - Max Schaub (American Political Science Review, 2021)
How does poverty influence political participation? This question has interested political scientists since the early days of the discipline, but providing a definitive answer has proved difficult. This article focuses on one central aspect of poverty—the experience of acute financial hardship, lasting a few days at a time. Drawing on classic models of political engagement and novel theoretical insights, I argue that by inducing stress, social isolation, and feelings of alienation, acute financial hardship has immediate negative effects on political participation. Inference relies on a natural experiment afforded by the sequence of bank working days that causes short-term financial difficulties for the poor. Using data from three million individuals, personal interviews, and 1,100 elections in Germany, I demonstrate that acute financial hardship reduces both turnout intentions and actual turnout. The results imply that the financial status of the poor on election day can have important consequences for their political representation.
doi:10.7910/DVN/ZCEQPS
Keywords: 300